An Explanatory Study of the Usefulness of Sustainable Relationship of Event Organizer Industry in Indonesia - Wahdiyat Moko (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
MICE business has undergone an accelerated development giving growing opportunity for event organizer industries. Therefore it causes an unvoidable competition among event organizer companies, especially in Indonesia where the MICE business has growing significantly in the past decade. This research explores the expected sustainable relationship between event organizer company and the event industry’s company owner. Using qualitative research with phenomenological approach with in depth interview of nine owner of event organizer companies and event – the research revealed that a sustainable relationship between the event organizer company and event industry’s company owner influences three important aspects such as = mutual benefit, company policies, and interpersonal relationships. In relate with healthy relationship, the form of relationship done by an event organizer aimed at creating a sustainable relationship with event industry’s company owner that indicated by event quality, creativity, trust, and loyalty. In acknowledging the results, further research can address the relationship between event quality, creativity, trust and customer loyalty, and the business performance.